Pengaruh Nct Dream sebagai Brand Ambassador dan Brand Image terhadap Perilaku Impulse Buying pada Produk Mie Instan Lemonilo - Ida Bagus Nyoman Udayana; Pingky Octavian; Ambar Lukitaningsih; Agus Dwi Cahya (LPPM Institut Nasional Laa Roiba Bogor, 2023)
The use of brand ambassadors has recently become a trend and is widely used in various products. Popular culture from South Korea brings new impacts to the business world, one of which is in product promotion or marketing. This study aims to determine: (1) the effect of NCT Dream as a brand ambassador on impulse buying behavior on instant noodle products lemonilo, (2) influence of brand image on impulse buying behavior lemonilo instant noodle products. (3) the influence of the NCT Dream brand ambassador and brand image together on impulse buying on Lemonilo instant noodle products. This study is a quantitative study using survey methods so that the population in this study are K-pop fans who live in Yogyakarta who know about NCT Dream and Lemonilo products. In taking samples using purposive sampling technique. Data collection uses a questionnaire method that has been tested for validity and reliability. This study uses a sampling technique by distributing questionnaires to take a sample of 75 people so that they can be tested for validity and reliability. With a 95% confidence level, the findings of this study indicate that brand ambassadors have a significant effect on impulse buying and brand image has a significant effect on impulse buying, and brand ambassadors and brand image have a joint effect on impulse buying behavior. This finding has implications for lemonilo products that the use of brand ambassadors can improve brand image and affect impulse buying behavior. Keywords: Brand Ambassadors; Brand Image; Impulse Buying Behavior